Achieving Microparticles with Cell‐Instructive Surface Chemistry by Using Tunable Co‐Polymer Surfactants. (25th June 2020) - Dundas, Adam A.; Cuzzucoli Crucitti, Valentina; Haas, Simon; Dubern, Jean‐Frédéric; Latif, Arsalan; Romero, Manuel; Sanni, Olutoba; Ghaemmaghami, Amir M.; Williams, Paul; Alexander, Morgan R.; Wildman, Ricky; Irvine, Derek J.
Abstract: A flow‐focusing microfluidic device is used to produce functionalized monodisperse polymer particles with surface chemistries designed to control bacterial biofilm formation. This is achieved by using molecularly designed bespoke surfactants synthesized via catalytic chain transfer polymerization. This novel approach of using polymeric surfactants, often called surfmers, containing a biofunctional moiety contrasts with the more commonly employed emulsion methods. Typically, the surface chemistry of microparticles are dominated by unwanted surfactants that dilute/mask the desired surface response. Time of flight secondary ion mass spectrometry (ToF‐SIMS) analysis of particles demonstrates that the comb‐graft surfactant is located on the particle surface. Biofilm experiments show how specifically engineered surface chemistries, generated by the surfactants, successfully modulate bacterial attachment to both polymer films, and microparticles. Thus, this paper outlines how the use of designed polymeric surfactants and droplet microfluidics can exert control over both the surface chemistry and size distribution of microparticle materials, demonstrating their critical importance for controlling surface‐cell response. Abstract : A droplet microfluidic approach is used to produce functionalized monodisperse particles. Synthesized polymer surfactants (surfmers) containing a biofunctional material of choice are used to replace conventional surfactants. These surfmers increase/decrease the formation of Pseudomonas aeruginosa biofilms compared to functionalized particles. This demonstrates the ability to change the function of microparticles simply by changing the surfmer used.